Short‐term outcome after singular hydraulic EsoFLIP dilation in patients with achalasia: A feasibility study. Issue 9 (11th May 2020) - Schnurre, Larissa; Murray, Fritz Ruprecht; Schindler, Valeria; Runggaldier, Daniel; Fischbach, Lara; Bordier, Valentine; Pohl, Daniel
Abstract: Background: Achalasia is a chronic esophageal motility disorder characterized by impaired relaxation of the lower esophageal sphincter, determined by an elevated integrated relaxation pressure (IRP > 15 mm Hg) and absent peristalsis. Goal of treatment is facilitation of flow across the EGJ but minimizing postinterventional reflux. A new advanced hydraulic dilation technology, the esophageal functional luminal imaging probe (EsoFLIP), allows dynamic monitoring of hollow organ dimensions while performing hydraulic dilation. The aim of our study was to evaluate the treatment response after single EsoFLIP dilation in achalasia patients. Methods: Dilation was performed under endoscopic control with the EsoFLIP device using a self‐developed dilation algorithm. Symptom scores were assessed by the Eckardt score (ES) before and 1‐4 weeks after intervention. Esophageal emptying before and after intervention was recorded with timed barium esophagogram. Key Results: We studied 28 consecutive untreated achalasia patients (8 female) with a median age of 43 years (range 19‐82 years) undergoing their first dilation performed with the EsoFLIP, aiming at a maximum dilation diameter of 25 mm. Total ES was significantly reduced from 7 at baseline to 2 postintervention ( P < .001). The median height of the barium column after 5 minutes was significantly reduced from 4.5 cm at baseline to 1.7 cm ( P = .0087). No major complications occurred. Conclusions & Inferences: We found good efficacy in both subjective and objective short‐term treatment outcome after singular EsoFLIP dilation in treatment‐naive achalasia patients. Our findings suggest that EsoFLIP is a promising dilation technology that should be further studied in a larger, controlled setting with longer follow‐up. Abstract : Goal of achalasia treatment is the facilitation of flow across the EGJ. In this study, we present results of a singular dilation with the esophageal functional luminal imaging probe (EsoFLIP). FLIP technology allows dynamic monitoring of hollow organ dimensions while performing hydraulic dilation, enabling physicians an individually tailored treatment approach for each patient. We found good efficacy in both subjective and objective short term treatment outcome after singular, individualized EsoFLIP dilation in treatment naïve achalasia patients.